Oncogenic Viral Prevalence in Invasive Vulvar Cancer Specimens From Human Immunodeficiency Virus–Positive and -Negative Women in Botswana. Issue 4 (1st May 2014) - Tesfalul, Martha; Simbiri, Kenneth; Wheat, Chikoti M.; Motsepe, Didintle; Goldbach, Hayley; Armstrong, Kathleen; Hudson, Kathryn; Kayembe, Mukendi K.; Robertson, Erle; Kovarik, Carrie
Abstract : Objective: The primary aim of this study was to describe the prevalence of select oncogenic viruses within vulvar squamous cell carcinoma (VSCC) and their association with human immunodeficiency virus (HIV) status in women in Botswana, where the national HIV prevalence is the third highest in the world. Methods: A cross-sectional study of biopsy-confirmed VSCC specimens and corresponding clinical data was conducted in Gaborone, Botswana. Polymerase chain reaction (PCR) and immunohistochemistry (IHC) viral testing were done for Epstein-Barr virus, human papillomavirus (HPV) strains, and Kaposi sarcoma herpesvirus, and PCR viral testing alone was done for John Cunningham virus. Results: Human papillomavirus prevalence by PCR was 100% (35/35) among tested samples. Human papillomavirus type 16 was the most prevalent HPV strain (82.9% by PCR, 94.7% by either PCR or IHC). Kaposi sarcoma herpesvirus prevalence by PCR had a significant association with HIV status ( P = 0.013), but not by IHC ( P = 0.650). Conclusions: The high burden of HPV, specifically HPV16, in vulvar squamous cell cancer in Botswana suggests a distinct HPV profile that differs from other studied populations, which provides increased motivation for HPV vaccination efforts. Oncogenic viruses Kaposi sarcoma herpesvirus and Epstein-Barr virus were also more prevalent in our study population, although their potential role in vulvar squamous cell cancer pathology is unclear.